PENGEMBANGAN KOMPETENSI ENTREPRENEUR DALAM MEMBANGUN SIKAP DAN JIWA KEWIRAUSAHAAN MELALUI PEMBELAJARAN BERBASIS PROYEK PADA PESERTA DIDIK - Salma Kusuma Listiani; Nisrina Luthfiya Azam; Yusnita Hikmawati; Amrullah, Muhammad Agung; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The high rate of educated unemployment in Indonesia, particularly among vocational high school graduates, which reached 8.90% (BPS, 2024), indicates a gap between the competencies taught in schools and the needs of the workforce. This study aims to analyze the effectiveness of Project-Based Learning (PjBL) as a strategy for developing entrepreneurial competencies and fostering entrepreneurial attitudes and spirit in students. The method used was library research with a descriptive qualitative approach through analysis of relevant scientific literature. The study results indicate that each stage of PjBL—from project planning and scheduling, implementation, monitoring, presentation, and evaluation—systematically stimulates the development of entrepreneurial character, encompassing creativity, discipline, responsibility, resilience, self-confidence, and communication skills. Furthermore, PjBL has been shown to encourage a shift in students' mindsets from a fixed mindset to a growth mindset, which is an essential foundation for an adaptive entrepreneurial spirit. This study recommends a six-stage PjBL entrepreneurship instructional framework that holistically integrates cognitive, affective, and conative aspects as a guide for educators in designing effective entrepreneurship learning.